Determination of Polysaccharides in Undaria pinnatifida by Ionic Liquid-Modified Silica Gel Size Exclusion Chromatography. (2nd September 2018) - Lee, Yu Ri; Ma, Wanwan; Row, Kyung Ho
ABSTRACT: Ionic liquid-modified silica particles with a large pore size were synthesized and used as the stationary phase for size exclusion chromatography coupled with a refractive index detector for the determination of polysaccharides, such as fucoidan, alginic acid, and laminarin from Undaria pinnatifida (seaweed). The molecular weight of polysaccharide was determined by a dextran standard curve (5–1100 kDa). The ionic liquid-modified silica column exhibited excellent size exclusion properties in separating laminarin from other components. The 1-butyl-3-methyl-imidazolium bis-(trifluoromethylsulfonyl)-amino silica column has superior resolution in laminarin separation than the other columns because the amino-group in ionic liquid provide π–π interactions due to aromaticity of the ring structure, which enhances the effect of the hydroxyl group in the target compound separation. The concentrations of polysaccharides were calculated using a standard linear equation to be 0.332–0.484 mg/g of fucoidan, 0.207–0.301 mg/g of alginic acid, and 0.154–0.297 mg/g of laminarin.